Talent development environments in Norwegian age-specific national teams in handball and ice hockey - Mehus, I.; Aspvik, N. P.; Sæther, S. A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The Talent Development Environment Questionnaire (TDEQ-5) (1), has been used in the Norwegian context to investigate the TDE of male players in soccer academies (2). However, the Norwegian version of the TDEQ-5 has not been tested for factorial validity. Furthermore, to the best of our knowledge, no previous studies have compared how female and male athletes experience their TDE across national teams in separate team sports. This study aims to test the Norwegian version of the TDEQ-5 through confirmatory factor analysis (CFA) for a five-factor structure, (a) long-term development focus (LTD), (b) communication (COM), (c) alignment of expectations (AOE), (d) holistic quality preparation (HQP), and (e) support network (SN). We also aim to compare how female and male athletes experience the TDE across different team sports.